The idea of freedom - from socialist beginnings to a liberal world view in the political and historical fiction of Mario Vargas Llosa - Ahnert, Friedrich (2023)
In the end, there are seven decisive Peruvian and South American novels by Mario Vargas Llosa that emblematically portray the emergence of Vargas Llosa’s world view – from his socialist convictions as a writer in exile from 1959 until 1971, towards the moderation in his philosophy in the 1970s to mid-1980s, as well as maturity since the 1990s of his, by then, liberal and cosmopolitan thought. Independent socialism, rationalist pragmatism, and globalised liberalism are just the key terms for the main transformations in the author’s intellect and literary reflection in his essays and writings, in particular for Vargas Llosa’s political and historical fiction. These novels are: La ciudad y los perros (I), Conversación en La Catedral (II), La guerra del fin del mundo (III), Historia de Mayta (IV), El héroe discreto (V), Cinco esquinas (VI) and Travesuras de la nin͂a mala (VII). Starting off with his renowned critique of an authoritarian and militarist education system in the Lima-based La ciudad y los perros – turning seemingly rebellious class behaviour into fundamental criticism against the leading social and cultural authorities of Peru during the early to mid-50s –, Vargas Llosa continues, in his subsequent novels, to criticise socially as well as politically authoritarian behaviour on a – however, this time – society-wide scale. In Conversación en La Catedral unjust political government as well as the radical questioning of the oligarchic and socially conservative status quo is portrayed. However, with the abandonment of the author’s radically left-wing side, in both his political commitment and his work, a new, much more critical literary portrayal can be observed in his fiction, regarding the neglect of Sartrean positions and the adoption of Camusian and Popperian criticism regarding revolt, revolution, or ideological destruction. In both La guerra del fin del mundo and Historia de Mayta utopia and revolution are condemned, and a universal path towards humanity and a rationalist approach to societal conflicts is proposed. With socialism’s ultimate failure at the very end of Historia de Mayta – signalling a programmatic shift of Vargas Llosa’s world view from social-democratic towards liberal convictions –, individual liberty is promoted as an integral part of human freedom and cosmopolitanism for the future generations of Peruvians – politically, by the embodiment of main figure Julieta in Cinco esquinas, and economically as well as morally, by either the main figures Felicíto and Ismael in El héroe discreto, or Lily and Ricardo in Travesuras de la niña mala.